Contribution of repeated infections in asthma persistence from preschool to school age: Design and characteristics of the PreDicta cohort. Issue 4 (10th April 2018) - Xepapadaki, Paraskevi; Bachert, Claus; Finotto, Susetta; Jartti, Tuomas; Konstantinou, George N.; Kiefer, Alexander; Kowalski, Marek; Lewandowska‐Polak, Anna; Lukkarinen, Heikki; Roumpedaki, Eirini; Sobanska, Anna; Sintobin, Ina; et al.
Abstract: Background: The PreDicta cohort was designed to prospectively evaluate wheeze/asthma persistence in preschoolers in association with viral/microbial exposures and immunological responses. We present the cohort design and demographic/disease characteristics and evaluate unsupervised and predefined phenotypic subgroups at inclusion. Methods: PreDicta is a 2‐year prospective study conducted in five European regions, including children 4‐6 years with a diagnosis of asthma as cases and healthy age‐matched controls. At baseline, detailed information on demographics, asthma and allergy‐related disease activity, exposures, and lifestyle were recorded. Lung function, airway inflammation, and immune responses were also assessed. Power analysis confirmed that the cohort is adequate to answer the initial hypothesis. Results: A total of 167 asthmatic children (102 males) and 66 healthy controls (30 males) were included. Groups were homogeneous in respect to most baseline characteristics, with the exception of male gender in cases (61%) and exposure to tobacco smoke. Comorbidities and number and duration of infections were significantly higher in asthmatics than controls. 55.7% of asthmatic children had at least one positive skin prick test to aeroallergens (controls: 33.3%, P  = .002). Spirometric and exhaled nitric oxide values were within normal limits; only baseline FEV0.5 and FEV1 reversibility values were significantly different between groups. Viral infections were the most common triggers (89.2%) independent of severity, control, or atopy; however, overlapping phenotypes were also common. Severity and control clustered together in an unsupervised analysis, separating moderate from mild disease. Conclusions: The PreDicta cohort presented no differences in non‐asthma related measures; however, it is well balanced regarding key phenotypic characteristics representative of "preschool asthma".